A Cross-Sectional Study for a Reference Model of Body Composition in Japanese Children Aged 3 to 10 Years - Keisuke Teramoto; Kodo Otoki; Erina Muramatsu; Yui Kataoka; Chika Oya; Yujiro Ishihara; Shuichi Komiya (International journal of school health (Online), 2023)
Background: The purpose of this study was to clarify the standard values of body composition for Japanese preschool and postschool-age children according to age and gender. Methods: The population of this cross-sectional study comprised 4,289 children (2,183 boys and 2,106 girls) aged 3 to 10 years and they were assessed during the period of 2003-2018. Anthropometric variables and body composition were measured using bioelectrical impedance analysis. The cut-off points for body mass index (BMI) calculated using Cole’s LMS method were set at the 25th and 75th percentile values for age and sex to provide a reference model for Japanese children. Differences among age and sex groups were analyzed by two-way ANOVA (P<0.05). Results: Height and weight increased significantly with age irrespective of sex. BMI component showed a higher fat-free mass index (FFMI) in boys and a higher fat mass index (FMI) in girls with transition from early childhood. These features were more pronounced when expressed in terms of quantity (fat mass or fat-free mass, kg), but the same result was obtained when expressed as an index (FMI or FFMI, kg/m2). Conclusion: Based on subjects from a large data set, this study established age- and sex-related body composition standards for Japanese before- and after-school children. There were also clear gender and age differences in body composition at this age. The results of this study will serve as basic data for various future pediatric studies.